Occurrence of sleep-disordered breathing in individuals with 22q11.2 deletion syndrome and its relationship with nasal obstruction and cardiorespiratory capacity - Spilari, Sarah (2025)
Introduction: 22q11.2 Deletion Syndrome (22q11.2DS), also known as DiGeorge Syndrome or Velocardiofacial Syndrome, presents multisystemic manifestations, including cardiac, gastrointestinal, craniofacial malformations, and sleep-disordered breathing, which can impact quality of life. Objective: To determine the occurrence of obstructive sleep-disordered breathing in individuals with 22q11.2DS and assess its relationship with nasal patency and cardiorespiratory capacity. Methods: Eleven patients (mean age 10.6±3.64 years) with molecular (n=6) or clinical (n=5) diagnoses of 22q11.2DS were evaluated. Questionnaires on sleep disorders, as Pediatric Sleep Questionnaire (PSQ) and Sleep Disturbance Scale for Children (SDSC) in subscales Sleep Disturbance Breathing (SDB) and Excessive Daytime Sleepiness (EDS), oral breathing, and nasal patency (CQ-5 and VAS) were administered. The 6-Minute Walk Test (6MWT) was conducted to assess cardiorespiratory capacity. A significance level of 5% (p<0.05) was adopted. Results: Positive scores for obstructive sleep apnea (OSA) were found in 54% of patients on the PSQ and 18% on the SDSC, with a positive correlation between PSQ and SDB (p=<0,05 r=0,84), and PSQ with EDS (p=<0,03 r=0,63). Daytime oral breathing was observed in 65% and nighttime oral breathing in 81%, while nasal obstruction was present in 54% of the individuals (CQ-5). The mean distance covered in the 6MWT was 401.67m (±94.02), with physiological increases in BORG escale, heart rate, respiratory frequency, and systolic blood pressure post-exercise. Diastolic blood pressure rose from 71.25 mmHg (±13.30) to 88.33 mmHg (±9.83) and showed a significant positive correlation with PSQ (p<0,05 r=0,76). Conclusion: Children and adolescents with 22q11.2DS have a high prevalence of OSA symptoms and are predominantly oral breathers with impaired nasal patency. Increased diastolic pressure during exercise may indicate future cardiovascular risk, highlighting the need for cardiovascular monitoring.